2016
DOI: 10.1155/2016/2920108
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine and/or Acetylcarnitine Deficiency as a Cause of Higher Levels of Ammonia

Abstract: Blood carnitine and/or acetylcarnitine deficiencies are postulated in the literature as possible causes of higher ammonia levels. The aim of this study was to investigate if the use of valproic acid, the age of the patients, or certain central nervous system pathologies can cause carnitine and/or acetylcarnitine deficiency leading to increased ammonia levels. Three groups of patients were studied: (A) epileptic under phenytoin monotherapy (n = 31); (B) with bipolar disorder under valproic acid treatment (n = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 39 publications
(45 reference statements)
4
32
0
Order By: Relevance
“… 4 , 5 The prevalence of symptomatic hyperammonemia caused by VPA is unknown, and the condition is thought to be rare in adults. However, in a study carried out by our group, 6 almost one-third of adult patients (8 of 28 patients) developed ammonia levels higher than the reference range, although only one of these patients exhibited unequivocal symptoms (encephalopathy). L-Carnitine (LCAR) is commonly used as an antidote in acute intoxication with VPA, 7 but its use in chronic treatment is reserved for the pediatric setting.…”
Section: Introductionmentioning
confidence: 62%
“… 4 , 5 The prevalence of symptomatic hyperammonemia caused by VPA is unknown, and the condition is thought to be rare in adults. However, in a study carried out by our group, 6 almost one-third of adult patients (8 of 28 patients) developed ammonia levels higher than the reference range, although only one of these patients exhibited unequivocal symptoms (encephalopathy). L-Carnitine (LCAR) is commonly used as an antidote in acute intoxication with VPA, 7 but its use in chronic treatment is reserved for the pediatric setting.…”
Section: Introductionmentioning
confidence: 62%
“…Acetylcarnitine performs major functions as a cofactor for the transport of long-chain fatty acids through the mitochondrial membrane [38]. However, previous research has demonstrated that acetylcarnitine deficiency leads to increased ammonia levels in the body [39]. Our former research has also proved that the expression a hepatic protein (histidine ammonia-lyase, HAL) involved in ammonia elimination was increased in sheep under OG conditions [4].…”
Section: Discussionmentioning
confidence: 87%
“…Ammonia levels in some of these patients were higher than the upper limit of the normal range in blood (25-94 μg/dL). Our research group has been studying increased ammonia levels in patients under VPA treatment [32,33]. High levels of ammonia in the brain can be the cause of seizures as ammonia easily crosses the blood-brain barrier, and in the brain, it can conjugate with α-ketoglutarate to form glutamate.…”
Section: Resultsmentioning
confidence: 99%